Impact of operating, financialand combined leverage on shareholder's return and market capitalization: evidence from selected sectors in colombo stock exchange in sri lanka. - Thulasika, M.; Vani, S.; Kirushika, S.; Saranya, G.; Kirishanthy, R. (University of Jaffna, 2016)
This study identify the impact of Operating leverage, financial leverage, and Combined leverage on shareholder's returns and market capitalization of the bank finance and insurance, beverage food and tobacco and hotels and travels sectors which are listed in Colombo Stock Exchange in Sri Lanka. Leverage is any technique that amplifies investor profits or losses. Its most commonly used to describe the use of borrowed money to magnify profit potential (financial leverage), but it can also describe the use of fixed assets to achieve the same goal (operating leverage). Leverage is the advantageous condition of having a relatively small amount of cost yield a relatively high level of returns. Leveraging is rarely a viable strategy for the individual investor. The present study explores the impact of operating, financial and combined leverage on shareholder's return and market capitalization. In this study, independent variables are degree of operating leverage, degree of financial leverage and degree of combined leverage, Dependent variables are shareholders return and market capitalization and also firm size is considered as control variable. Sample size of this research is fifteen companies which are collected from annual report of selected listed companies in CSE, over the period from 2010 to 2015. This study use the tools of descriptive statistic, correlation analyse and Regression analyse based on SPSS Techniques. The results revealed that, Operating leverage has significantly negative relationship with SR (-0.277*) and Financial leverage has significantly negative relationship between MC (-0.310**). Further Operating leverage, and financial leverage has impact on shareholder's return and market capitalization.
Keywords: Colombo stock exchange; Leverage; Market capitalization; Shareholders returns